EFFECTIVENESS OF HEALTH EDUCATION ABOUT WOUND HEALING PROCESS TO KNOWLEDGE LEVELS IN POST-CIRCUMSITION FAMILY IN SUKOHARJO DISTRICT - Putri Halimu Husna; Rohmat Widiyanto (Akademi Keperawatan Giri Satria Husada Wonogiri, 2020)
Background : Circumcision was the act of removing penile valve through minor surgery that aims as an action that was religiously recommended and good for health. This study was to determine the effectiveness of health education about wound healing processes on the level of knowledge in post-circumcision families.Objective : Arranging resume of Surgical Medical nursing care in post circumcision families to determine the effectiveness of health education about the wound healing process of the level of knowledge in post circumcision families.Methods : This study used qualitative research with a case study design. The research was conducted at the circumcision house in Sukoharjo February 28, 2019. The population in this study were all post-circumcision families in the circumcision of Sukoharjo as many as 15 people, the sample in this study was taken using inclusion criteria and homogeneity of the sample as many as 3 people. This study used a questionnaire measurement tool.Results : The results of the assessment of all respondents obtained subjective results the majority of respondents never and did not know about post-circumcision wound care, the advantages and disadvantages of not treating circumcised wounds properly. The level of knowledge of the respondents were 50%, 57.14% and 53.57% in the poor category. After 20 minutes of health education, the results of all respondents with a level of knowledge of 71.43% were in the moderate category, 85.7% and 92.86% in the good category.Conclusion: Health education can increase respondents' knowledge about wound healing after circumcision. Suggestions for further research is to measure skills in treating wounds in post-circumcision families after health education.